Investigation of Nutrition Habits and Ergogenic Aid Uses of Arm Wrestling Athletes during Training and Competition Periods - Adem YAPICI (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2022)
This research was conducted to examine the nutritional habits and ergogenic aid use of arm wrestling athletes during training and competition periods. 215 licensed athletes, who have been active in arm wrestling for an average of 4 years, voluntarily participated in the study. The study was designed as a quantitative survey study. Participants were determined by simple random sampling method. The data were collected through “Google Forms”. Frequency and percentage analyzes were performed on the obtained data using the Microsoft Excel program. According to analyzed results, it was determined that the participants showed similar eating habits during the training and competition periods. Besides, it was determined that majority of the participants did not use ergogenic aids.